MILD HYDROTHERMAL SYNTHESIS, CRYSTAL STRUCTURE AND MORPHOLOGY OF LiV2O5 - Celik Gul, Gulsah; Kurtulus, Figen (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Anode materials with high storage capacity and high power density attract considerable interest because of recent advances in Li-ion battery used electronic devices. Vanadium based oxides are the one possible group. LiV2O5 was synthesized by hydrothermal method at 3 days (72 hours) and 180 ºC. Structural characterization was performed by powder X-ray diffraction, fourier transform infrared spectroscopy. Morphology was scanned by scanning electron microscopy with energy disperse X-ray analysis. The first time synthesized material is crstallisized in orthorombic system with unit cell parameters a = 11.31, b = 9.552, c = 3.585 and space group Pmn21 (31).